Indoor/Outdoor Air Quality Assessment at School near the Steel Plant in Taranto (Italy) - A. Di Gilio; G. Farella; A. Marzocca; R. Giua; G. Assennato; M. Tutino; G. de Gennaro (Advances in Meteorology)
This study aims to investigate the air quality in primary school placed in district of Taranto (south of Italy), an area of high environmental risk because of closeness between large industrial complex and urban settlement. The chemical characterization of PM2.5 was performed to identify origin of pollutants detected inside school and the comparison between indoor and outdoor levels of PAHs and metals allowed evaluating intrusion of outdoor pollutants or the existence of specific indoor sources. The results showed that the indoor and outdoor levels of PM2.5, BaP, Cd, Ni, As, and Pb never exceeded the target values issued by World Health Organization (WHO). Nevertheless, high metals and PAHs concentrations were detected especially when school were downwind to the steel plant. The I/O ratio showed the impact of outdoor pollutants, especially of industrial markers as Fe, Mn, Zn, and Pb, on indoor air quality. This result was confirmed by values of diagnostic ratio as B(a)P/B(g)P, IP/(IP + BgP), BaP/Chry, and BaP/(BaP + Chry), which showed range characteristics of coke and coal combustion. However, Ni and As showed I/O ratio of 2.5 and 1.4, respectively, suggesting the presence of indoor sources.